2001
DOI: 10.1097/00002030-200109280-00008
|View full text |Cite
|
Sign up to set email alerts
|

Response to first protease inhibitor- and efavirenz-containing antiretroviral combination therapy The Swiss HIV Cohort Study

Abstract: Treatment with efavirenz-, compared with PI-based regimens, appeared to result in a superior virological response but no difference in immunological or clinical efficacy. The relevance of these observations remains to be determined in studies with longer follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 16 publications
3
32
0
Order By: Relevance
“…Our findings are consistent with those of other studies in demonstrating the importance of the initial HAART regimen in the probability and rate of achieving virological suppression [11,12,20]. As indicated here, individuals starting on ritonavir-boosted PI regimens or NNRTI regimens were more likely to achieve suppression than patients on unboosted PI regimens.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with those of other studies in demonstrating the importance of the initial HAART regimen in the probability and rate of achieving virological suppression [11,12,20]. As indicated here, individuals starting on ritonavir-boosted PI regimens or NNRTI regimens were more likely to achieve suppression than patients on unboosted PI regimens.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, choice of initial antiretroviral regimen plays an important role in the time it takes to achieve a viral load that is undetectable [11,12]. While the long-term clinical benefits of earlier suppression are unclear, achievement of suppression earlier reduces the length of time one carries detectable virus and may allow more immediate CD4 T-cell reconstitution [13].…”
Section: Introductionmentioning
confidence: 99%
“…In long-term controlled clinical trials, the combination of efavirenz, emtricitabine and tenofovir disoproxil fumarate has demonstrated durable efficacy and safety (Friedl et al, 2001;Gallant et al, 2006;Squires et al, 2003). Recently published data from Gallant et al, (2006) have demonstrated that the combination of efavirenz, emtricitabine and tenofovir disoproxil fumarate provides superior outcomes in terms of virologic suppression, CD4 cell response and adverse events in treatment-naive patients compared with the previous gold-standard regimen of fixed dose zidovudinelamivudine plus efavirenz.…”
Section: Introductionmentioning
confidence: 99%
“…Opportunistic Infect.). Finally, recent data comparing the virologic effect of NNRTI-and PI-based antiretroviral combinations suggest that the use of NNRTI is associated with a faster and more frequent initial virologic response (14,23).…”
Section: Discussionmentioning
confidence: 99%